Altered Metabolites in the Occipital Lobe in Migraine Without Aura During the Attack and the Interictal Period - Zhang, Luping; Huang, Jinwen; Zhang, Zhengxiang; Cao, Zhijian (Frontiers in Neurology, 2021)
ABSTRACT Background: Although there have been many magnetic resonance spectroscopy (MRS) studies of migraine, few have focused on migraines during an attack. Here, we aimed to assess metabolite changes in the brain of patients with migraine, both during an attack and in the interictal phase. Methods: Six patients (one man and five women, mean age: 39±10 years) with migraine without aura during the attack (MWoA-DA); thirteen patients (three men and ten women, mean age: 31±9 years) with migraine without aura during the interictal period (MWoA-DI); and thirteen healthy controls (HC) (four men and nine women, mean age: 31±9 years) were studied. All subjects underwent an MRS examination focusing on the occipital lobe. Metabolite changes were investigated among three groups. Results: The MWoA-DA patients had lower glutathione/total creatine ratio (GSH/tCr) than the MWoA-DI patients and HC. Further, MWoA-DI patients showed lower total choline/total creatine ratio (tCho/tCr) than those in the other two groups. The GSH/tCr ratio was positively correlated with attack frequency in the MWoA-DI group. The tCho/tCr ratio was positively correlated with attack frequency and Migraine Disability Assessment Scale (MIDAS) scores in the MWoA-DA group. Conclusion: The present study suggests the existence of distinct pathophysiological states between the MWoA-DA and MWoA-DI groups. Neuronal dysfunction is a possible predisposing factor for migraine attack onset, along with oxidative stress and inflammation.